2012
DOI: 10.1371/journal.pone.0034980
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Loading Increases Osteogenic Gene Expression and Cortical Bone Volume in Mature and Middle-Aged Mice

Abstract: There are conflicting data on whether age reduces the response of the skeleton to mechanical stimuli. We examined this question in female BALB/c mice of different ages, ranging from young to middle-aged (2, 4, 7, 12 months). We first assessed markers of bone turnover in control (non-loaded) mice. Serum osteocalcin and CTX declined significantly from 2 to 4 months (p<0.001). There were similar age-related declines in tibial mRNA expression of osteoblast- and osteoclast-related genes, most notably in late osteob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 41 publications
3
55
1
Order By: Relevance
“…We have previously applied tibial compression to BALB/c mice across their life span [17, 18]. Our initial study reported no decline in periosteal mechano-responsiveness with aging when comparing 7– to 22-month-old male BALB/c mice [17], a finding that was unexpected and at odds with prior reports in humans, rats and C57Bl/6 mice [5, 8].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have previously applied tibial compression to BALB/c mice across their life span [17, 18]. Our initial study reported no decline in periosteal mechano-responsiveness with aging when comparing 7– to 22-month-old male BALB/c mice [17], a finding that was unexpected and at odds with prior reports in humans, rats and C57Bl/6 mice [5, 8].…”
Section: Discussionmentioning
confidence: 84%
“…Scan resolution was 21 μm (70 kV, 114 μA, 100 ms integration time). This scanning protocol has proven sensitive enough to detect longitudinal bone changes [17, 18], and represents a compromise that sacrifices optimal image quality in order to reduce radiation exposure. Negative radiation side effects have been noted by others who scanned at a higher resolution (10 μm) and more frequently (every 5 days) [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA isolation was performed using Trizol (Life Technologies, Carlsbad, CA) and RNeasy Mini kit (Qiagen, Germantown, MD) as described previously [13]. Briefly, individual cancellous and cortical samples were pulverized in liquid nitrogen-cooled flasks (Mikrodismembrator S, Sartorius Stedim Biotech, Bohemia, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MicroCT images are widely used to determine 3D micro-morphological parameters of rodent bone [31][32][33]. Being a non-invasive technique microCT can be used to monitor structural changes of bone in longitudinal studies of living mice [34][35][36][37]. Recently longitudinal in vivo microCT was combined with 3D image registration, automated volumetric segmentation and morphological evaluation to volumetrically quantify spatial bone (re)modeling (formation and resorption) events on the bone surfaces of living mice [35,36,38].…”
Section: Introductionmentioning
confidence: 99%